Healthy behaviors among teenagers studying in schools in the urban and rural areas of Western Poland - Donata Woitas-Ślubowska; Ewelina Żyżniewska-Banaszak; Anna Skarpańska-Stejnborn (Kazimierz Wielki University, 2016)
Introduction: Unhealthy behaviors are related to the increased risk of morbidity and mortality. Reduction of the risk is possible, although it requires modification of the unhealthy behaviors. This change is possible in all stages of life, however it is most effective in its early phases. A well documented correlation between health-related behaviors and morbidity and mortality makes them an important aspect of public health. Aim: The aim of this study was the recognition  of health-related behaviors among boys and girls studying in the schools of the urban and rural areas of Western Poland and also pointing out a group of youth that should be targeted with specialized health education programmes. Method: This study was conducted on a group of 845 middle school students (14-16 yrs), attending randomly selected middle schools in urban and rural areas located in the Western Poland. An anonymous auditory survey was conducted. The survey consisted of 31 close-ended questions about the demographic and socioeconomic status, and health-related behaviors. In this paper in the statistical evaluation of the accumulated data concerned relationships between health-related behaviors and gender and place of study. Results: A widespread occurrence of unhealthy behaviors was observed. Many participants admitted to unhealthy nutritional habits, and, although less frequently, tobacco use, drinking alcohol and low physical activity. The area in which the students were located played an important part in the nutritional behaviors of boys and with the use of tobacco and the physical activity of girls. The group at the most risk of unhealthy behaviors were the girls studying in the urban middle schools and the boys studying in the rural middle schools. Conclusion: The unhealthy behaviors are a reason for maintaining a regular health education of the middle school students. This education should consider specific educational needs related to the sex and students` place of study.